ANALISIS KEHILANGAN AIR (NON REVENUE WATER) PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA BAU BAU - Risma Niswati Tarman; Tamrin Tamrin (Pusat riset dan Inovasi Nasional, 2022)
Water loss can be defined as the difference between the recorded amount of water in the system and the amount of water out of the system shown, in a water supply system is not entirely produced water installations reach consumer. Usually there is a leak here and there, called the loss of water. Then to reduce or minimize the water loss rate needed the right solution. One of solution that can be used is the Non Revenued Water (NRW) program. NRW can be defined as water that can be measured and a known amount of be chased but can not or may not be income, but it can be justified. The one of the methodologies that can be used to determine the amount (NRW) is a method of infrastructure leakage index (ILI) used Software WBEasycalc3. Water loss rate is the percentage ratio between water loss and the amount of water distributed in piped water network, while the water balance is calculated based on the amount of incoming water flow, consumption meter-Revenue, customer meter inaccuracies, water loss and physical loss. Both of two magnitudes in the ILI value is calculated by using Table Matrix Target that compiled by regulators of water service DKI Jakarta.